A conductimetric investigation of phenomena in extremely dilute aqueous solutions - Faure, Pierre Knobel (Rhodes University, Faculty of Science, Department of Chemistry, 1957)
1. The apparatus used in this investigation is fully described, and a new method is outlined for the calibration of bridge resistances "in situ". 2. A chart is given for the accurate correction of weights in air to weights in vacuum for a range of temperatures extending from 10° to 28°C, and for pressures from 690 to 730 mm. 3. An automatic recycling still has been designed for the continuous production of "ultra-pure" water. This still is capable of delivering daily, in routine operation, 16 l. of water of conductivity less than 100 nm/cm after aeration with "C0₂- and NH₃-free" air. 4. A very soluble layer appears to form on the surface of' glass when it is dried; this layer is readily removed on contact with water. 5. The removal of carbon dioxide and of ammonia from aqueous solution by aeration with an indifferent gas has been fully investigated, and it has been shown that these gases can be completely eliminated by such a process. Whereas the carbon dioxide is removed fairly rapidly, however, the ammonia, whether present alone or together with carbon dioxide, only goes out of solution rather slowly. 6. It has been shown that ammonia is adsorbed from aqueous solution on the glass walls of the cell. 7. There does not appear to be any ammonium bicarbonate in the residual impurity left in the "ultra-pure" water obtained from the still; the impurity can, in fact, be regarded as neutral salt with sufficient accuracy for most purposes. 8. The resistance change which accompanies any variation in the rate of bubbling of the stirring gas through the water has been investigated, but no solution has been found as to the cause of this change. 9. A comparison has been made of the efficiency of different gases for stirring purposes, and it seems that, for general work, nitrogen is by far the most suitable of the common gases. 10. The extrapolation to be used for converting resistances to their values at infinite frequency appears ...
Keywords: Adsorption; Solution (Chemistry)